Efektifkah sistem pendidikan guru di Indonesia? - Aziz, Aulia Luqman; Safira, Shifa; Maura, Diva; Azzahra, Anisa; Dwiajeng, Alfi; Diva, Afifah; Khoiruddin, Abd. Wahid (Ma'arif Journal of Education, Madrasah Innovation and Aswaja Studies, 2022)
The purpose of this study was to determine the politics of education and educational practice as reflected in the teacher education process, the provision of professional teachers, the learning process, the education evaluation system, and teacher welfare in Indonesia. This research uses a qualitative approach. The results showed that the qualifications of an educator will determine the direction of educational development in the future. Education is a benchmark for the progress of a nation and civilization. Certified educators are required to be able to carry out their obligations professionally and seriously in accordance with the field of science they master. Professional educators are followed by faith, piety, good personality, ability, sincerity, and potential to improve the quality of education in Indonesia. Facts in the field, many education personnel who teach not based on their scientific background, so knowledge transfer cannot be carried out optimally.